THE ROLE OF BRAND IMAGE IN MEDIATING THE EFFECT OF PRODUCT QUALITY ON REPURCHASE INTENTIONS BOKASHI RUB OIL IN DENPASAR CITY - Pradnya Dewi, Putu Andini; Rahanatha, Gede Bayu; Kerti Yasa, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023, 2023)
Indonesia’s traditional medicine industry is growing rapidly. Bokashi Rub Oil is one of a traditional medicine in the form of rub oil that combines coconut arrack oil with Effective Microorganism (EM) technology. The proper strategy must be implemented by Bokashi Rub Oil to make consumers feel interested and repeat purchases. The purpose of this resesearch is to explain how product quality affect brand image and repurchase intentions. The number of samples taken as 152 respondents using a questionnaire, which was carried out in Denpasar City. A non probability sampling and purposive sampling technique were used to select the sample. Using SPSS for Windows, path analysis was used as the method of data analysis. The analylis results findings demonstrate that not all hypotheses are accepted. The effect of product quality on repurchase intentions is significant positive, the effect of brand image on repurchase intentions is significant positive. On the other hand, product quality has an insignificant positive effect on brand image, brand image is unable mediate the effect of product quality on repurchase intentions